Basic fibroblast growth factor predicts cardiovascular disease occurrence in participants from the Veterans Affairs Diabetes Trial - Zimering, Mark B.; Anderson, Robert J.; Ge, Ling; Moritz, Thomas E.; Duckworth, William C. (Frontiers in Endocrinology, 2013)
Aim: Cardiovascular disease is a leading cause of morbidity and mortality in adults with type 2 diabetes mellitus. The aim of the present study was to test whether plasma basic fibroblast growth factor (bFGF) levels predict future cardiovascular disease (CVD) occurrence in adults from the Veterans Affairs Diabetes Trial. Methods: Nearly four- hundred veterans, 40 years of age or older, having a mean baseline diabetes duration of 11.4 years were recruited from outpatient clinics at six geographically distributed sites in the Veterans Affairs Diabetes Trial (VADT). Within the VADT, they were randomly assigned to intensive or standard glycemic treatment, with follow-up as much as seven and one-half years. Cardiovascular disease occurrence was examined at baseline in the patient population and during randomized treatment. Plasma bFGF was determined with a sensitive, specific two-site enzyme-linked immunoassay at the baseline study visit in all 399 subjects. Results: One hundred-five first cardiovascular events occurred in these 399 subjects. The best fit model of risk factors associated with the time to first cardiovascular disease occurrence (in the study) over a seven and one-half year period had as significant predictors: prior cardiovascular event, (hazard ratio [HR] 3.378; 95% confidence intervals [CI] 3.079- 3.807; P < .0001), baseline plasma bFGF (HR 1.008; 95% CI 1.002-1.014; P =.01), age, (HR 1.027; 95% CI 1.004-1.051; P =.019), baseline plasma triglycerides, (HR 1.001; 95% CI 1.000-1.002; P =.02) and diabetes duration-treatment interaction (P =.03). Intensive glucose-lowering was associated with significantly decreased hazard ratios for CVD occurrence (0.38-0.63) in patients with known diabetes duration of 0-10 years, and non-significantly increased hazard ratios for CVD occurrence (0.82-1.78) in patients with longer diabetes duration. Conclusion: High level ofplasma basic fibroblast growth factor is a predictive biomarker of future cardiovascular disease